On-Farm Diversification in an Agriculturally-Dominated Landscape Positively Influences Specialist Pollinators - Guzman, Aidee; Chase, Marissa; Kremen, Claire (Frontiers in Sustainable Food Systems, 2019)
Agricultural practices can either contribute to pollinator decline or provide opportunities to support pollinator communities. At the landscape-scale, agriculture can have negative impacts on pollinators, especially pollinators that specialize on limited floral or nesting resources. While increasing floral resources at the field-scale is positive for pollinator communities, little is known about how it affects specialist bees that depend on a specific pollen source (oligoleges). We studied pollinators on small-scale farms that contrasted in crop diversity (monocultures versus polycultures), embedded in the intensively managed agriculture region of the San Joaquin Valley in California, to understand how wild bee communities and specialist bees would respond to field-scale diversification practices. We used squash (Cucurbita pepo) as our focal crop, because it is visited by both specialist pollinators, “squash bees” in the genera Peponapis and Xenoglossa, and by generalist bees like those in the genera Apis and Agapostemon. We hypothesized that there would be a greater number of squash bees on monoculture farms, which have abundant squash flowers, than on polyculture farms. Contrary to our predictions, we found that increasing the number of non-squash floral resources at the field-scale in agroecosystems supports a greater abundance of squash bees but has no effect on the diversity of bees visiting squash flowers. This pattern of increased abundance was consistent for other wild bees and the total number of bees (i.e. including honey bees), but not for honey bee abundance alone. Further, the abundance of pollinators increased or remained the same on polyculture farms throughout the morning while decreasing on monoculture farms, suggesting that as squash flowers start to close in midmorning, bees on the monocultures go elsewhere because no other floral resources co-occur. However, they remain on the polycultures where other resources co-occur. Thus, on-farm diversification may be an important refuge for both specialist bees and other pollinator species that are vulnerable to floral resource simplification and loss in landscapes dominated by monoculture agriculture.